Uni-index variable angle ultrasonic phased array probe - CARODISKEY THOMAS J (2007)
An ultrasonic probe (2) used for inspecting a workpiece (44) comprising a delay body (8) and a transducer array (4) having a plurality of transducer elements (6) mounted on the delay body (8). The plurality of transducer elements (6) of the transducer array (4) are mounted on the curved outer surface of the delay body (8). The transducer elements (6) in the array of elements are equidistant from a center of the radius of curvature (14) of the delay body (8), so that sound waves simultaneously generated by two or more of the transducer elements (6) arrive at the center of the radius, also referred to as the origin point (16), at the same time. The reflected sound passing through the index point received by a transducer in the array (4) is not subject to a time delay resulting from the geometry of the delay body (8).